Protocolos a seguir en el área de postoperatorio mediato para disminuir el riesgo de infecciones nosocomiales Hospital Alfredo Noboa Montenegro octubre 2018 – abril 2019 - Ramírez Chimborazo, Jorge Fernando (2019)
The research elaborates on the adequate fulfillment of de protocols, since currently the improper fulfillment on then represents one of the main causes of the nosocomial infections, thus increasing the rate of hospital morbidity and mortality. The purpose of this study was to identify the correct implementation of the protocols used in the area of the mediate postoperative period for prevention of risk of nosocomial infections “Hospital Alfredo Noboa Montenegro” October 2018 – April 2019. The type of research that was used was the qualitative and quantitative directed as a main focus, inductive since it allowed an analysis and precise synthesis of the variables of study in relation to the contents, so it was used the method historical since logical that to develop this research was needed to investigate the background, causes and consequences. Information collected from the place where begins the problem allowing you to collect the data necessary for the execution of the project, through the application of survey and observation guide informal since I helped to focus attention on what you are interested in. of the sample studied 20% adequately meets protocols, 23% comply whit deficiency, while 27% do not comply and unknown protocols, so it is clearly a big problem. It is possible to conclude that, to develop nosocomial infections, a relationship between the adequate fulfillment of the protocols and the days of the patient stay, by which we fail to decrease infections, costs, morbidity and mortality in hospitals.